2000
DOI: 10.1002/1099-0739(200008)14:8<411::aid-aoc24>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic compounds in terrestrial organisms. IV. Green plants and lichens from an old arsenic smelter site in Austria

Abstract: Two lichens and 12 green plants growing at a former arsenic roasting facility in Austria were analyzed for total arsenic by ICP-MS, and for 12 arsenic compounds (arsenous acid, arsenic acid, dimethylarsinic acid, methylarsonic acid, arsenobetaine, arsenocholine, trimethylarsine oxide, the tetramethylarsonium cation and four arsenoriboses) by HPLC-ICP-MS. Total arsenic concentrations were in the range of 0.27 mg As (kg dry mass) À1 (Vaccinium vitis idaea) to 8.45 mg As (kg dry mass) À1 (Equisetum pratense). Ars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 100 publications
(60 citation statements)
references
References 21 publications
4
56
0
Order By: Relevance
“…Some of the challenges surrounding homogenization can be addressed by drying or freezing samples prior to this step; increasing the ease by which homogenization can take place, and ending microbial activity which may otherwise disrupt the chemical equilibrium between species. Commonly employed techniques are air drying [15; 58], oven-drying [63], freezing to between -20°C to -80 ˚C [64], freeze-drying [65] and cryogenic freezing with liquid nitrogen [59; 66].…”
Section: Sampling and Sample Pre-treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the challenges surrounding homogenization can be addressed by drying or freezing samples prior to this step; increasing the ease by which homogenization can take place, and ending microbial activity which may otherwise disrupt the chemical equilibrium between species. Commonly employed techniques are air drying [15; 58], oven-drying [63], freezing to between -20°C to -80 ˚C [64], freeze-drying [65] and cryogenic freezing with liquid nitrogen [59; 66].…”
Section: Sampling and Sample Pre-treatmentmentioning
confidence: 99%
“…An example of the use of HPLC-ICP-MS, shown in Table 1 is in the determination of arsenic species in lichens and plants near a decomissioned arsenic smelter site in Austria [65], whilst sequential extractions were used to separate As species in lichens to assess As air pollution in another study [77] ( Table 1). Extractions were performed on powdered lichens using water, CaCl 2 and H 3 PO 4 respectivelyIt was concluded that biotransformation of As may have occured, where the lichens were thought to methylate the As species as a protective measure.…”
Section: Arsenicmentioning
confidence: 99%
“…Therefore, the abundance and distribution of arsenic compounds within red beet plants did not differ significantly from the behavior of arsenic compounds in other plant species and the results were expectable. Comparable results have been presented by other authors within different plant species [16,19,20,44].…”
Section: Contents Of Investigated Elements and Arsenic Compounds In Rmentioning
confidence: 99%
“…Transformation and translocation of arsenic compounds among plant tissues is strongly dependent on plant species and/or soil characteristics [17]. The occurrence of individual arsenic compounds in higher plants and their distribution into different plant tissues are strongly dependent on plant species [18,19]. As(III), As(V), DMA, MA, trimethylarsine oxide, the tetramethylarsonium ion, and one arsenoribose were identified in green plant species grown at arsenic contaminated sites; the compounds and their concentrations differ with plant species [19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation